Prime-boost vaccination strategy in women with high-grade, noncervical anogenital intraepithelial neoplasia: clinical results from a multicenter phase II trial. Issue 3 (1st April 2006) - Fiander, A. N.; Tristram, A. J.; Davidson, E. J.; Tomlinson, A. E.; Man, S.; Baldwin, P. J.; Sterling, J. C.; Kitchener, H. C.
Abstract : The objective of this study was to determine the clinical effectiveness of a prime-boost human papillomavirus (HPV) vaccine regimen. A nonrandomized phase II prime-boost vaccine trial was conducted. Women with biopsy-proven anogenital intraepithelial neoplasia (AGIN) 3 were vaccinated with three doses of a recombinant fusion protein comprising HPV 16, E6/E7/L2 (TA-CIN) followed by one dose of a recombinant vaccinia virus encoding HPV 16 and 18 E6/E7 (TA-HPV). Clinical responses were evaluated by serial photographs, symptomatology, and biopsies before and after vaccination. Twenty-nine women were vaccinated; 27 with vulval intraepithelial neoplasia 3 and 2 with vaginal intraepithelial neoplasia grade 3. Clinical responses were seen in five women (17%), with one complete and five partial responses. Fifteen women (62%) had symptomatic improvement. No serious adverse effects were recorded. This is the first trial of a prime-boost vaccination regimen using heterologous HPV vaccines (TA-CIN followed by TA-HPV) in the management of AGIN. Since the prime-boost approach in this cohort offered no significant advantages over single TA-HPV vaccination, there are no further studies planned using this protocol. Future studies are warranted to define responders to immunotherapy.